THE PARAMEDIC ULTRASOUND IN CARDIAC ARREST STUDY. Issue 12 (18th November 2016) - Reed, MJ; Gibson, L; Black, P; Dewar, A; Clegg, G; Short, S
Abstract : Objectives & Background: The Edinburgh 3RU paramedics have some advanced training in cardiac arrest (CA) management The PUCA study aimed to see whether pre-hospital paramedics can ▸ be trained to perform and [2] interpret pre-hospital ELS ▸ retain ELS performance and interpretation skills ▸ perform satisfactory pre-hospital ELS ▸ perform pre-hospital ELS without impacting CA care Methods: Phase 1 – Testing/purchasing a suitable ultrasound machine Phase 2 – Formal classroom based training: one-day training course with practical and moulage sessions. Phase 3 – Field based training. Phase 4 – Prospective observational study of pre-hospital paramedic ELS using saved ultrasound clips and wearable camera videos. Results: During classroom based training, all paramedics could obtain parasternal (PS) and subxiphoid (SX) images. ▸ 88% of attempts in both views were successful in the pulse check window. ▸ Theoretical knowledge improved (mean pre vs post course score 54% vs 89%; p<0.001) and at 10 weeks was non-significantly reduced (82%; p=0.13) but less so than practical performance (75% SX success, 25% PS success). ▸ By Sep 2015, 8 of 11 paramedics who attended initial training, had passed a triggered competency assessment and were practicing pre-hospital ELS independently. ▸ Between 23rd June 2014 and 31st Jan 2016, seven 3RU paramedics attended 45 patients suffering out-of-hospital CA where resuscitation was attempted and the Venue 40 ultrasound machine was available and used. ▸ 80% of first paramedic ELS attempts produced an adequate view which was excellent/good/satisfactory in 68%. ▸ 44% of views were obtained within the pulse check window with a median time off the chest of 17 seconds (IQR 13–20). ▸ A decision to perform ELS was communicated in 67% and the pulse check counted aloud in 60%. ▸ A manual pulse check was seen to be performed in a quarter of patients and the monitor rhythm checked in 38%. ▸ All decision changing scans involved a decision to stop resuscitation. Conclusion: Paramedics can perform focussed ELS in the classroom, integrate attempts into simulated CA scenarios and retain some of this knowledge. ▸ They obtain good ELS views in the pre-hospital environment but with longer hands off the chest times. ▸ The quality of life support may be reduced with less obvious pulse and monitor checking. ▸ Paramedic pre-hospital ELS is more likely to be performed in patients where discontinuation of resuscitation is being considered. ▸ Further training should focus on improving ELS situational awareness.